Planting dreams : shaping Australian gardens. - Aitken, Richard; State Library of New South Wales (Sydney : State Library of New South Wales, 2016)
"Explores the ideas and influences that have shaped the way we make, use and enjoy our gardens." -- Publisher's website.
Exhibition catalogue: 3 September 2016 - 15 January 2017
Keywords: Gardens -- Australia -- Exhibitions; Gardening -- Australia -- Exhibitions; Gardens in art -- Exhibitions; Australian